2002
DOI: 10.1177/088840640202500203
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Textbooks: A Rationale for a More Inclusive Use of Literature in Preservice Special Education Teacher Programs

Abstract: The role of any teacher education program in the field of special education has been to prepare its graduates to become successful classroom teachers. Teacher education programs have constantly searched for the best available practices to educate future teachers. Historically, textbooks have been the predominant form of information dissemination within the university culture. The use of textbooks, bound by structure and limited by content, has narrowed the knowledge base that teacher education graduates bring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Accordingly, the qualitative training of teachers who will take part in inclusive practices aims to primarily promote positive attitudes in teachers (Morrison and Rude, 2002). Related with this, Soodak et al (1998) found that the selfefficacy perceptions of teachers are strongest predictor of their attitudes toward inclusion.…”
Section: Introductionmentioning
confidence: 89%
“…Accordingly, the qualitative training of teachers who will take part in inclusive practices aims to primarily promote positive attitudes in teachers (Morrison and Rude, 2002). Related with this, Soodak et al (1998) found that the selfefficacy perceptions of teachers are strongest predictor of their attitudes toward inclusion.…”
Section: Introductionmentioning
confidence: 89%
“…Several factors can be considered as effective in forming teachers' consensus in terms of special needs students and inclusive education. For instance, the fact that special needs students are described with negative characteristics and deficits as individuals with learning problems who are impulsive, aggressive, self-destructive and uncontrolled in university textbooks can result in establishing an over generalized perspective towards these individuals (Güner-Yıldız, Sazak-Pınar and Melekoğlu, 2014;Morrison and Rude, 2002). As a result of this point of view, teachers may regard "special needs" as a cause for problem behaviors (Smith, 2000) and tend to refuse to take with special needs students or pay sufficient attention to them even if these students are registered in their classrooms (Cook, Cameron and Tankersley, 2007).…”
Section: Introductionmentioning
confidence: 99%